This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Lemma: If P ( x ) is a polynomial with integer coefficients, then x − y ∣ P ( x ) − P ( y ) for every x , y integer.
Proof: Letting P ( x ) = i = 0 ∑ n a i x i with a i being an integer for every i we obtain
P ( x ) − P ( y ) = i = 0 ∑ n a i x i − i = 0 ∑ n a i y i = i = 0 ∑ n a i ( x i − y i )
Clearly x − y ∣ x i − y i for i ≥ 0 (since x i − y i = ( x − y ) ( x i − 1 + x i − 2 y + . . . + x y i − 2 + y i − 1 ) for i > 0 and x i − y i = 1 − 1 = 0 for i = 0 ), which means that
x − y ∣ i = 0 ∑ n a i ( x i − y i ) = P ( x ) − P ( y ) .
Applying the lemma for the polynomial described in the problem with x = 2 0 1 8 and y = 2 0 1 5 we would have
3 = x − y ∣ P ( x ) − P ( y ) = 1 − 2 0 1 6 = − 2 0 1 5
but 3 ∤ ( − 2 0 1 5 ) so there does not exist such a polynomial.